Using Item Response Theory to Develop and Validate Item Bank in Elementary Grade Mathematics - Dildar, Muazzam; Ahmed Abdullah, Nauman (JSE, 2025)
In Pakistan, educational institutions use a variety of assessments, of which tests are the most often used type at all levels. The creation of item banks is one of the contemporary test trends. The development and validation of an item bank in mathematics for elementary-grade pupils was the aim of this study. The study's approach was quantitative, and a math test for grade 8 was created using a table of specifications. Initially, the test had 150 items. After applying item difficulty and discrimination index, 36 items were excluded due to poor values on these indices. The way these items were changed, the discrimination index and difficulty level of 18 items were both fairly good. Due to the regulated difficulty level and discrimination index, 96 items were also included. In the end, the researchers obtained 114 items for the study's target audience, which was intended to be administered to 720 Grade 8 pupils in the Lahore division. ConQuest software was used to evaluate the data, and it was discovered that 33 of the items were good, 31 were fair, 30 were put in the poor grade category, and 22 were eliminated. These resources can help teachers better prepare Grade 8 pupils for the Punjab Examination Commission. To enhance the value of assessment, item bank may be developed for all educational levels.